Human resource management strategy for enhancing competitive advantage - Sundari; Novemy Triyandari Nugroho (Institute of Computer Science (IOCS), 2023)
This research seeks to elaborately describe the actual trends related to the competitive advantages gained from strategic human resource management efforts. The research method in this study is descriptive qualitative with a literature study approach. The sources of data taken are data sources derived from scientific publications relevant to the theme of the paper, consisting of scientific journals, news, opinions and other credible and congruent sources. The results of the study found that employee-based potential development is one of the effective strategies. The roles and strategic human resource roles and functions should be geared towards generate the company's key competitiveness and manage the company's capabilities to be more flexible and dynamic. This strategy is expected to able to stimulate continuous innovation that will integrate human resource management behaviour, so that the company can be managed to be more adaptive to environmental changes.